Aluminum alloy cable and preparation method thereof
Through the synergistic effect of modified basalt fibers and modified resins, the problem of degradation in performance of aluminum alloy cables in extreme environments is solved, significantly improving the mechanical and corrosion resistance of the cable sheath, and extending the service life of the cable.
Patent Information
- Application Number
- CN202411675876.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The mechanical properties and corrosion resistance of aluminum alloy cables in extreme environments are degraded, making it difficult to meet the requirements of use under extreme temperature conditions.
The synergistic effect of modified basalt fibers and modified resins is adopted to improve the compatibility and binding force between basalt fibers and resin matrix through acid oxidation treatment and surfactant modification, and a specific inorganic filler and flame retardant are added to form High performance cable sheath.
It significantly improves the mechanical strength, corrosion resistance, extreme temperature resistance and flame retardant properties of the cable sheath, extends the service life of the cable and improves reliability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables, and in particular relates to an aluminum alloy cable and a preparation method thereof. Background Art
[0002] Aluminum alloy cable is a wire or cable made of aluminum alloy. Compared with traditional copper cables, aluminum alloy cables have the advantages of light weight, high tensile strength, strong wear resistance and good flexibility. Aluminum alloy cables are used in various industries such as construction industry, power transmission, industrial facilities, and transportation infrastructure.
[0003] Aluminum alloy cables include aluminum alloy conductors and sheaths covering the outside of the aluminum alloy conductors. Due to the large number of application scenarios of aluminum alloys, the external environment becomes complex and changeable, which makes the cable sheaths extremely susceptible to the external environment. Once the sheath fails, the electrical performance of the aluminum alloy conductor inside the cable will be affected. The selection of sheath materials is crucial for aluminum alloy cables, because it not only needs to protect the cable from external physical damage, but also needs to resist chemical corrosion. In a humid or salty environment, the cable sheath may be corroded, affecting the overall performance and life of the cable. In alkaline or acidic soils, the aging process of the sheath material may be accelerated, resulting in a decrease in the protection ability of the cable. Therefore, the selected sheath material needs to be able to resist ultraviolet radiation and chemical erosion to ensure the long-term stable operation of the cable under various environmental conditions.
[0004] At present, the main methods to improve the environmental resistance of cable sheath are as follows: (1) Use special paint or coating to cover the surface of the cable sheath to isolate the corrosive medium.
[0005] (2) Use composite materials to make the sheath. Compound the metal sheath with plastic or rubber materials to provide good mechanical protection and enhance corrosion resistance.
[0006] (3) Consider strengthening the sheath structure during design, such as using a double-layer sheath or adding an armor layer, adopting a compression structure or other special structural designs, which can improve the tightness and mechanical strength of the cable.
[0007] Through these methods, existing technologies can largely solve the corrosion resistance and mechanical strength problems of cable sheaths, thereby extending the service life of cables and ensuring their safe and reliable operation. However, aluminum alloy cables are often used in some extreme environments. In extremely cold environments, extremely hot environments, and extremely cold and hot alternating environments, the mechanical properties and corrosion resistance of aluminum alloy cables will be significantly reduced. Aluminum alloy cables have very poor tolerance to extreme environments.
[0008] Therefore, there is an urgent need for an aluminum alloy cable that can maintain mechanical properties and corrosion resistance in extreme environments. Summary of the invention
[0009] The purpose of the present invention is to provide an aluminum alloy cable and a preparation method thereof, so as to solve the problem that the above aluminum alloy cable is easily affected in extreme environments, resulting in the decrease of its mechanical properties and corrosion resistance. The present invention significantly improves the performance of the cable sheath in multiple aspects, including mechanical properties, corrosion resistance, extreme temperature resistance, flame retardancy and processing performance, through the synergistic effect of modified basalt fiber and modified resin, thereby improving the overall reliability and service life of the cable.
[0010] To achieve the above object, the present invention provides an aluminum alloy cable in a first aspect, comprising an aluminum alloy conductor and a sheath coated on the outside of the aluminum alloy conductor, wherein the sheath comprises the following raw materials in parts by weight: 100-120 parts of modified resin; 45~55 parts of modifier and enhancer; 40~50 parts of inorganic filler; Flame retardant 5~30 parts; 10~20 parts of plasticizer; Antioxidant 0.1~3 parts; 0.5~1 part of lubricant; The preparation method of the modified reinforcing agent is: Concentrated sulfuric acid and water are mixed, and then hydrogen peroxide is added to obtain an acid oxidation solution, and then basalt cellulose is added to the acid oxidation solution, soaked at 60-90° C. for 2-4 hours, washed with deionized water until neutral, and dried to obtain a first modified basalt fiber; Add 3-5 parts of the first modified basalt fiber to a mixed aqueous solution formed by 1-3 parts of sodium α-olefin sulfonate and 1-3 parts of sodium cocoyl aminopropionate, soak at room temperature for 24-48 hours, take out, wash and dry, to obtain a second modified basalt fiber; 1-3 parts of silicon carbide, 4-6 parts of silicon dioxide and 1-3 parts of titanium dioxide are mixed to obtain a mixture, and then a mixed aqueous solution formed by 0.5-1.2 parts of γ-aminopropyltriethoxysilane is added to the mixture, and the mixture is stirred evenly to form a dispersion. Then, the second modified basalt fiber is added to the dispersion, and the mixture is reacted at 100-120° C. for 1-3 hours, and then naturally cooled to room temperature, filtered, washed, and dried to obtain a modified reinforcing agent.
[0011] The average particle size of silicon carbide is 100nm and the specific surface area is 30~40m 2 / g, purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd., model number is ZT-C100A.
[0012] The average particle size of silicon dioxide is 20 nm, and it was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd. with model number ZT-SP20P.
[0013] The average particle size of titanium dioxide is 5 nm and it was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd. with model number ZT05.
[0014] The cable sheath is an important component to protect the internal conductor and insulation layer of the cable from the influence of the external environment. It needs to have good corrosion resistance and sufficient mechanical strength to ensure the long-term reliable operation of the cable. The sheath material may react with the acid and alkali substances in the soil, causing material degradation. At present, the corrosion resistance and mechanical properties of the sheath are improved by selecting suitable materials. However, in the application process, it is still difficult to meet the actual requirements for the mechanical properties and corrosion resistance of the cable sheath. The present invention adopts basalt fiber to modify the formula of the cable sheath. Basalt fiber is an inorganic non-metallic material with good high temperature resistance, corrosion resistance and high mechanical strength. By using it to improve the formula of the cable sheath, on the one hand, the corrosion resistance of the cable sheath can be improved. Basalt fiber has high chemical stability and is not easy to react with most acids and alkalis, so the corrosion resistance of the sheath can be improved; basalt fiber shows good stability in an electrochemical environment, which helps to prevent the occurrence of electrochemical corrosion. On the other hand, the mechanical properties of the cable sheath can be improved. Basalt fiber has high strength and rigidity, which can significantly improve the mechanical strength of the cable sheath and reduce damage caused by physical damage; the addition of basalt fiber can improve the wear resistance of the sheath material and reduce damage caused by wear.
[0015] The present invention adds basalt fiber to the cable sheath to improve the corrosion resistance and mechanical properties. The inventor tried to improve the corrosion resistance and mechanical properties of the cable sheath at extremely high or low temperatures by adding basalt fiber, but found that the effect was not ideal. The inventor continued to study and found that after the basalt fiber was modified in the present invention, the mechanical properties and corrosion resistance of the cable sheath in extreme environments can be significantly improved. The reason for the analysis is: the surface treatment of basalt fiber with concentrated sulfuric acid and hydrogen peroxide can increase the surface activity of basalt fiber, which is conducive to the subsequent combination with other materials. The use of surfactants such as sodium α-olefin sulfonate and sodium coconut aminopropionate can further improve the compatibility between basalt fiber and resin matrix, thereby improving the overall performance of the composite material. The introduction of inorganic fillers such as silicon carbide, silicon dioxide and titanium dioxide with specific parameters can further enhance the mechanical properties of the composite material, and γ-aminopropyltriethoxysilane as a coupling agent can promote the combination between these inorganic fillers and basalt fiber, thereby improving the performance of the overall composite material.
[0016] The present invention can improve the compatibility between basalt fiber and resin matrix by modifying basalt fiber, enhance the bonding force between the two, and thus improve the overall performance of the composite material. The modifier can fill the micropores on the surface of the basalt fiber, reduce the surface roughness, and reduce the adsorption of corrosive media. The modifier can also improve the dispersibility of the basalt fiber, avoid the formation of stress concentration areas in the composite material, and thus improve the mechanical properties of the material under extreme temperature conditions.
[0017] In addition, the basalt fiber in the present invention is subjected to the two steps of acid oxidation reaction and surfactant treatment before continuing to be mixed with silicon carbide, silicon dioxide and titanium dioxide. The two steps of acid oxidation treatment and surfactant treatment are indispensable and complement each other to jointly improve the compatibility between the basalt fiber and the resin matrix, thereby improving the tolerance of the cable sheath to environmental changes. If the basalt fiber is only subjected to acid oxidation treatment without surfactant treatment, the tolerance of the cable sheath in extreme environments will not reach a higher level. Acid oxidation modification generally uses an acid (such as concentrated sulfuric acid) and an oxidant (such as hydrogen peroxide) to treat the surface of the basalt fiber to change its surface properties. This method can increase the roughness and activity of the fiber surface, which helps to improve the bonding force between the fiber and the matrix material. However, only acid oxidation modification without the use of a surfactant may lead to the following problems: Although acid oxidation modification can improve the activity of basalt fiber surface, without the help of surfactant, the interfacial bonding strength between fiber and resin matrix may not be sufficient to cope with stress changes under extreme temperature conditions. This may lead to delamination or cracking of composite materials at high or low temperatures.
[0018] Acid oxidation modification alone may not be sufficient to completely improve the difference in thermal expansion coefficient between basalt fibers and matrix materials, which may lead to stress concentration when the temperature changes sharply, thus affecting the integrity and mechanical properties of the composites.
[0019] Acid oxidation modification usually increases the roughness of the fiber surface, which, while helpful in improving the bonding with the matrix, may also increase the adsorption of corrosive media in some cases, especially when surfactants are not used to further improve the surface properties.
[0020] Without the assistance of surfactants, there may be more defects at the interface between the basalt fiber and the matrix after acid oxidation treatment, and these defects will become the starting point of corrosion, thereby reducing the corrosion resistance of the composite material.
[0021] Preferably, the single filament diameter of the basalt fiber is 5.5-25 μm and the length is 6-10 mm.
[0022] Basalt fiber was purchased from Jiangsu Tianlong Basalt Continuous Fiber Co., Ltd., with a breaking strength of ≥2000MPa, an elastic modulus of ≥80Gpa, a breaking strength retention rate of ≥85% after heat treatment, and an acidity coefficient of ≥4.5.
[0023] Preferably, in parts by weight, the preparation method of the modified resin is: The polyvinyl chloride is added to a nitric acid solution and activated at 90-100°C for 3-5 hours, then washed with deionized water until neutral, and then dried at 80-100°C to obtain modified polyvinyl chloride; 10-20 parts of modified polyvinyl chloride, 5-10 parts of high-density polyethylene and 1-5 parts of silicone rubber are mixed, and then added into a twin-screw extruder for melt blending. During the extrusion process, 0.3-0.5 parts of azobisisobutyronitrile and 2-5 parts of epoxy acrylate are also added. The temperature of the twin-screw extruder is 180-220°C. After the mixture is cooled and formed, a modified resin is obtained.
[0024] Polyvinyl chloride was purchased from Nantong Nandao Plastic Co., Ltd. with a brand name of 7356, a tensile strength of ≥13 MPa, and an elongation at break of ≥250%.
[0025] High-density polyethylene was purchased from PetroChina Dushanzi Petrochemical Company with a grade of HD6070EA, a molecular weight of 40,000-300,000, a melt flow index of 6.5-8.0, and an Izod impact strength of 4 KJ / m 2 , tensile yield strength ≥ 23 Mpa, density 955-960 Kg / m 3 .
[0026] The silicone rubber was purchased from Shenzhen Jerry New Materials Co., Ltd. with a brand name of E630, a viscosity of 9000 cps, a tensile strength of 5.2 MPa, and an elongation of ≥470%.
[0027] The present invention modifies the basalt fiber on one hand to improve its compatibility with the resin matrix, and on the other hand modifies the resin to improve the high temperature resistance and low temperature resistance of the cable sheath.
[0028] At present, the resin matrix used in the preparation process of cable sheath is mostly a resin, among which polyvinyl chloride, as a common cable sheath material, has excellent insulation performance, good flame retardant performance, and wide applicability. However, when it is used in the cable sheath as a single resin, it has the problems of insufficient tensile strength, poor corrosion resistance, poor high temperature resistance and poor low temperature resistance. The present invention mixes polyvinyl chloride with silicone rubber and high-density polyethylene on the basis of polyvinyl chloride. Silicon rubber can improve the toughness of the material due to its elasticity, so that the cable sheath is not prone to brittle fracture when subjected to external force. High-density polyethylene also has good toughness, which can further improve the mechanical properties of the cable sheath. Therefore, the addition of silicone rubber and high-density polyethylene can be mixed with polyvinyl chloride to improve the corrosion resistance and mechanical properties of the cable sheath.
[0029] The inventors continued to study and found that simple physical mixing of polyvinyl chloride with silicone rubber and high-density polyethylene can improve the mechanical properties and corrosion resistance of the cable sheath, but failed to achieve good retention of the mechanical properties and corrosion resistance of the cable sheath in extremely high and low environments. The inventors found that continuing to modify polyvinyl chloride and polymerizing the modified polyvinyl chloride, silicone rubber and high-density polyethylene can further improve the mechanical properties and corrosion resistance of the cable sheath in extreme environments. This is because after the modified polyvinyl chloride is activated by acid, new reactive groups are generated on the surface, which increases the reactivity with other substances, and can also improve the interfacial bonding between PVC and other components and reduce interface defects. The presence of initiators and monomers promotes cross-linking between molecules, forming a denser network structure, further reducing the permeability of the corrosive medium, and also increasing the mechanical properties of the cable sheath.
[0030] Preferably, The mass concentration of concentrated sulfuric acid in the acid oxidation solution is 30-40%, and the mass concentration of hydrogen peroxide is 10-15%; The mass concentration of sodium α-olefin sulfonate is 5~8%, and the mass concentration of sodium cocoyl aminopropionate is 5~8%; The mass concentration of γ-aminopropyltriethoxysilane is 1~3%; The mass concentration of nitric acid solution is 20~40%.
[0031] Preferably, the inorganic filler is one or more of calcium carbonate, aluminum hydroxide and magnesium hydroxide.
[0032] Preferably, the flame retardant is one or more of zinc borate, melamine phosphate, and triphenylphosphonate.
[0033] Preferably, the plasticizer is one or more of dioctyl adipate, dioctyl sebacate, and tri(2-hydroxyethyl)phosphine.
[0034] Preferably, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] or 2,2-bis(4-hydroxyphenyl)propane.
[0035] Preferably, the lubricant is one or more of PE wax, stearic acid, solid paraffin, and calcium stearate.
[0036] A second aspect of the present invention provides a method for preparing an aluminum alloy cable, comprising the following steps: a) Add modified resin, modified reinforcing agent, inorganic filler, flame retardant, plasticizer, antioxidant and lubricant into a high-speed mixer, mix at 110-125°C for 5-8 hours to obtain a mixed material; b) At 150-200° C., the mixed material is extruded using an extruder and coated on the surface of the aluminum alloy conductor to form a sheath to obtain an aluminum alloy cable.
[0037] Therefore, the present invention adopts the above-mentioned aluminum alloy cable and its preparation method, which has the following beneficial effects: 1. By using multiply modified basalt fibers as reinforcing agents, the mechanical strength of the cable sheath is significantly improved, the tensile strength and compressive strength of the cable are enhanced, and the safety and reliability of the cable during installation and use are improved.
[0038] 2. The modified basalt fiber of the present invention is subjected to acid oxidation treatment and surfactant modification, which can effectively improve its corrosion resistance, thereby improving the chemical corrosion resistance of the entire cable sheath and extending the service life of the cable.
[0039] 3. The present invention improves the toughness of the material and enhances the tensile strength of the cable sheath by adding high-density polyethylene and silicone rubber. The use of modified resin, especially by adding components such as azobisisobutyronitrile and epoxy acrylate, improves the high and low temperature resistance of the cable sheath, so that it can still maintain good mechanical and electrical properties under extreme temperature conditions.
[0040] 4. The addition of flame retardants in the present invention can significantly improve the flame retardant properties of the cable sheath, reduce the risk of fire, and improve the safety of the cable.
[0041] 5. The present invention improves the fluidity and processability of the cable sheath material through the synergistic effect of the modified resin and basalt fiber, simplifies the manufacturing process and reduces the production cost.
[0042] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0043] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0044] Example 1 This embodiment provides an aluminum alloy cable, including an aluminum alloy conductor and a sheath covering the aluminum alloy conductor, wherein the sheath includes the following raw materials in parts by weight: 120 parts of modified resin; 50 parts of modification and reinforcing agent; 45 parts of inorganic filler; the inorganic filler is calcium carbonate.
[0045] 20 parts of flame retardant; the flame retardant is zinc borate.
[0046] 15 parts of plasticizer; the plasticizer is dioctyl adipate.
[0047] 0.5 parts of antioxidant; the antioxidant is 2,2-bis(4-hydroxyphenyl)propane.
[0048] 0.5 parts of lubricant; the lubricant is calcium stearate.
[0049] The preparation method of the modified reinforcing agent is: Concentrated sulfuric acid and water are mixed, and then hydrogen peroxide is added to obtain an acid oxidation solution, wherein the mass concentration of concentrated sulfuric acid in the acid oxidation solution is 30%, and the mass concentration of hydrogen peroxide is 12%, and then basalt cellulose is added to the acid oxidation solution, soaked at 80° C. for 3 hours, washed with deionized water until neutral, and dried to obtain a first modified basalt fiber; The single fiber diameter of basalt fiber is 5.5~25μm and the length is 6~10mm.
[0050] The basalt fiber was purchased from Jiangsu Tianlong Basalt Continuous Fiber Co., Ltd. and has good dispersibility, high temperature stability, low temperature crack resistance and fatigue resistance, a breaking strength ≥ 2000MPa, an elastic modulus ≥ 80Gpa, a breaking strength retention rate after heat treatment ≥ 85%, and an acidity coefficient ≥ 4.5.
[0051] Add 5 parts of the first modified basalt fiber to a mixed aqueous solution formed by 2 parts of sodium α-olefin sulfonate and 1 part of sodium cocoyl aminopropionate, wherein the mass concentration of the sodium α-olefin sulfonate is 8% and the mass concentration of the sodium cocoyl aminopropionate is 6%, soak at room temperature for 24 hours, take out, wash and dry, to obtain a second modified basalt fiber; 2 parts of silicon carbide, 5 parts of silicon dioxide and 3 parts of titanium dioxide are mixed to obtain a mixture, and then a mixed aqueous solution formed by 1 part of γ-aminopropyltriethoxysilane is added to the mixture, the mass concentration of γ-aminopropyltriethoxysilane is 2%, and the mixture is stirred evenly to form a dispersion. Then, the second modified basalt fiber is added to the dispersion, and after reacting at 110°C for 2 hours, it is naturally cooled to room temperature, filtered, washed, and dried to obtain a modified reinforcing agent.
[0052] The average particle size of silicon carbide is 100nm and the specific surface area is 30~40m 2 / g, purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd., model number is ZT-C100A.
[0053] The average particle size of silicon dioxide is 20 nm, and it was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd. with model number ZT-SP20P.
[0054] The average particle size of titanium dioxide is 5 nm and it was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd. with model number ZT05.
[0055] According to parts by weight, the preparation method of the modified resin is: After adding polyvinyl chloride into nitric acid solution and activating it at 95°C for 3 hours, the mass concentration of the nitric acid solution is 30%, it is washed with deionized water to neutrality, and then dried at 80°C to obtain modified polyvinyl chloride; polyvinyl chloride was purchased from Nantong Nandao Plastic Co., Ltd., with a brand number of 7356, a tensile strength of ≥13 MPa, and an elongation at break of ≥250%.
[0056] 15 parts of modified polyvinyl chloride, 8 parts of high-density polyethylene and 3 parts of silicone rubber were mixed and then added to a twin-screw extruder for melt blending. 0.4 parts of azobisisobutyronitrile and 3 parts of epoxy acrylate were also added during the extrusion process. The temperature of the twin-screw extruder was 180°C. After the mixture was cooled and formed, a modified resin was obtained.
[0057] High-density polyethylene was purchased from PetroChina Dushanzi Petrochemical Company with a grade of HD6070EA, a molecular weight of 40,000-300,000, a melt flow index of 6.5-8.0, and an Izod impact strength of 4 KJ / m 2 , tensile yield strength ≥ 23 Mpa, density 955-960 Kg / m 3 .
[0058] The silicone rubber was purchased from Shenzhen Jerry New Materials Co., Ltd. with a brand name of E630, a viscosity of 9000 cps, a tensile strength of 5.2 MPa, and an elongation of ≥470%.
[0059] Epoxy acrylate was purchased from Shanghai Koraman Reagent Co., Ltd., CAS: 71281-65-7.
[0060] Azobisisobutyronitrile was purchased from Shandong Yukang Chemical Co., Ltd., CAS: 78-67-1.
[0061] A method for preparing an aluminum alloy cable comprises the following steps: a) adding modified resin, modified reinforcing agent, inorganic filler, flame retardant, plasticizer, antioxidant and lubricant into a high-speed mixer, mixing at 120° C. for 5 hours to obtain a mixed material; b) At 170° C., the mixed material is extruded using an extruder and coated on the surface of the aluminum alloy conductor to form a sheath to obtain an aluminum alloy cable.
[0062] Example 2 The difference between this embodiment and embodiment 1 is that the formula of the cable sheath is different.
[0063] The sheath formula of this embodiment includes the following raw materials in parts by weight: 100 parts of modified resin; 45 parts of modifying and reinforcing agent; 40 parts of inorganic filler; Flame retardant 10 parts; 10 parts of plasticizer; 0.3 parts of antioxidant; 0.8 parts of lubricant.
[0064] Example 3 The difference between this embodiment and embodiment 1 is that the formula of the cable sheath is different.
[0065] The sheath formula of this embodiment includes the following raw materials in parts by weight: 110 parts of modified resin; 48 parts of modifying and reinforcing agent; 45 parts of inorganic filler; Flame retardant 28 parts; 18 parts of plasticizer; 2 parts of antioxidant; 1 part lubricant.
[0066] Comparative Example 1 The difference between this comparative example and Example 1 is that the modified reinforcing agent is basalt fiber.
[0067] Comparative Example 2 The difference between this comparative example and Example 1 is that the basalt fiber in the modified reinforcing agent is only subjected to acid oxidation treatment and is not subjected to surfactant treatment.
[0068] The preparation method of the modified reinforcing agent is: Concentrated sulfuric acid and water are mixed, and then hydrogen peroxide is added to obtain an acid oxidation solution, wherein the mass concentration of concentrated sulfuric acid in the acid oxidation solution is 30%, and the mass concentration of hydrogen peroxide is 12%, and then basalt cellulose is added to the acid oxidation solution, soaked at 80° C. for 3 hours, washed with deionized water until neutral, and dried to obtain a first modified basalt fiber; 2 parts of silicon carbide, 5 parts of silicon dioxide and 3 parts of titanium dioxide are mixed to obtain a mixture, and then a mixed aqueous solution formed by 1 part of γ-aminopropyltriethoxysilane is added to the mixture, the mass concentration of γ-aminopropyltriethoxysilane is 2%, and the mixture is stirred evenly to form a dispersion. Then, the first modified basalt fiber is added to the dispersion, and after reacting at 110°C for 2 hours, it is naturally cooled to room temperature, filtered, washed, and dried to obtain a modified reinforcing agent.
[0069] Comparative Example 3 The difference between this comparative example and Example 1 is that only silicon dioxide is used in the modified reinforcing agent to be mixed with the second modified basalt.
[0070] The preparation method of the modified reinforcing agent is: Concentrated sulfuric acid and water are mixed, and then hydrogen peroxide is added to obtain an acid oxidation solution, wherein the mass concentration of concentrated sulfuric acid in the acid oxidation solution is 30%, and the mass concentration of hydrogen peroxide is 12%, and then basalt cellulose is added to the acid oxidation solution, soaked at 80° C. for 3 hours, washed with deionized water until neutral, and dried to obtain a first modified basalt fiber; Add 5 parts of the first modified basalt fiber to a mixed aqueous solution formed by 2 parts of sodium α-olefin sulfonate and 1 part of sodium cocoyl aminopropionate, wherein the mass concentration of the sodium α-olefin sulfonate is 8% and the mass concentration of the sodium cocoyl aminopropionate is 6%, soak at room temperature for 24 hours, take out, wash and dry, to obtain a second modified basalt fiber; Ten parts of silicon dioxide are mixed to obtain a mixture, and then a mixed aqueous solution formed by adding one part of γ-aminopropyltriethoxysilane to the mixture, wherein the mass concentration of γ-aminopropyltriethoxysilane is 2%, and the mixture is stirred evenly to form a dispersion. Then, the second modified basalt fiber is added to the dispersion, reacted at 110° C. for 2 hours, naturally cooled to room temperature, filtered, washed, and dried to obtain a modified reinforcing agent.
[0071] Comparative Example 4 The difference between this comparative example and Example 1 is that the modified resin is replaced by a mixture of polyvinyl chloride, high-density polyethylene and silicone rubber, and the polyvinyl chloride in the modified resin is not acid-activated.
[0072] The specific preparation method of the modified resin is: 15 parts of polyvinyl chloride, 8 parts of high-density polyethylene and 3 parts of silicone rubber are mixed and then added into a twin-screw extruder for melt blending. During the extrusion process, 0.4 parts of azobisisobutyronitrile and 3 parts of epoxy acrylate are also added. The temperature of the twin-screw extruder is 180°C. After the mixture is cooled and formed, a modified resin is obtained.
[0073] Comparative Example 5 The difference between this comparative example and Example 1 is that no silicone rubber is added to the modified resin.
[0074] The specific preparation method of the modified resin is: The polyvinyl chloride was added into a nitric acid solution at 95°C for activation for 3 hours, the mass concentration of the nitric acid solution was 30%, the polyvinyl chloride was washed with deionized water until neutral, and then dried at 80°C to obtain a modified polyvinyl chloride; 18 parts of modified polyvinyl chloride and 8 parts of high-density polyethylene were mixed and then added into a twin-screw extruder for melt blending. 0.4 parts of azobisisobutyronitrile and 3 parts of epoxy acrylate were also added during the extrusion process. The temperature of the twin-screw extruder was 180°C. After the mixture was cooled and formed, a modified resin was obtained.
[0075] Comparative Example 6 The difference between this comparative example and Example 1 is that high-density polyethylene is not added to the modified resin.
[0076] The preparation method of the modified resin is: The polyvinyl chloride was added into a nitric acid solution at 95°C for activation for 3 hours, the mass concentration of the nitric acid solution was 30%, the polyvinyl chloride was washed with deionized water until neutral, and then dried at 80°C to obtain a modified polyvinyl chloride; 23 parts of modified polyvinyl chloride and 3 parts of silicone rubber were added into a twin-screw extruder for melt blending. 0.4 parts of azobisisobutyronitrile and 3 parts of epoxy acrylate were also added during the extrusion process. The temperature of the twin-screw extruder was 180° C. After the mixture was cooled and formed, a modified resin was obtained.
[0077] Comparative Example 7 The difference between this comparative example and Example 1 is that no initiator and grafting monomer are added to the modified resin.
[0078] The preparation method of the modified resin is: The polyvinyl chloride was added into a nitric acid solution at 95°C for activation for 3 hours, the mass concentration of the nitric acid solution was 30%, the polyvinyl chloride was washed with deionized water until neutral, and then dried at 80°C to obtain a modified polyvinyl chloride; 15 parts of modified polyvinyl chloride, 8 parts of high-density polyethylene and 3 parts of silicone rubber are mixed, and then added into a twin-screw extruder for melt blending. The temperature of the twin-screw extruder is 180°C. After the mixture is cooled and formed, a modified resin is obtained.
[0079] Comparative Example 8 The difference between this comparative example and Example 1 is that the modified resin is replaced by polyvinyl chloride.
[0080] Comparative Example 9 The difference between this comparative example and Example 1 is that low-density polyethylene is used in the modified resin.
[0081] The specific preparation method of the modified resin is: According to parts by weight, the preparation method of the modified resin is: After adding polyvinyl chloride into nitric acid solution and activating it at 95°C for 3 hours, the mass concentration of the nitric acid solution is 30%, it is washed with deionized water to neutrality, and then dried at 80°C to obtain modified polyvinyl chloride; polyvinyl chloride was purchased from Nantong Nandao Plastic Co., Ltd., with a brand number of 7356, a tensile strength of ≥13 MPa, and an elongation at break of ≥250%.
[0082] 15 parts of modified polyvinyl chloride, 8 parts of low-density polyethylene and 3 parts of silicone rubber were mixed and then added to a twin-screw extruder for melt blending. 0.4 parts of azobisisobutyronitrile and 3 parts of epoxy acrylate were also added during the extrusion process. The temperature of the twin-screw extruder was 180°C. After the mixture was cooled and formed, a modified resin was obtained.
[0083] Low-density polyethylene was purchased from Sinopec Qilu Petrochemical Company, with a grade of 2602TV43, a melt flow index of 2.1-2.9, and a density of 0.924-0.928 g / cm 3 , breaking strength ≥11.0 MPa.
[0084] Comparative Example 10 The difference between this comparative example and Example 1 is the type of silicone rubber in the modified resin.
[0085] The silicone rubber used in this comparative example was purchased from Shenzhen Jerry New Materials Co., Ltd., with a brand name of E640, a viscosity of 12000 cps, a tensile strength of 6.2 MPa, and an elongation of ≥400%.
[0086] Performance Testing The tensile strength and elongation at break of the cable sheaths prepared in Examples 1 to 3 and Comparative Examples 1 to 10 were tested according to standard GB / T 1040.3-2006.
[0087] The thermal deformation and 200° C. thermal stability time of the cable sheaths prepared in Examples 1 to 3 and Comparative Examples 1 to 10 were tested according to standard GB / T 8815-2008.
[0088] The low temperature (-50°C) impact embrittlement properties of the cable sheaths prepared in Examples 1 to 3 and Comparative Examples 1 to 10 were tested according to standard GB / T 5470-2008.
[0089] The aging resistance of the cable sheaths prepared in Examples 1 to 3 and Comparative Examples 1 to 10 was tested according to standard GB / T 1040.3-2006.
[0090] The cable sheath was placed in a 10% hydrochloric acid solution for 30 days, taken out and dried, and then the tensile strength and elongation at break of the cable sheaths prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 10 were tested according to standard GB / T1040.3-2006.
[0091] Table 1 Mechanical properties and corrosion resistance test results
[0092] Table 2 Extreme environment resistance performance test results
[0093] It can be seen from the above performance test results that the cable sheaths prepared in Examples 1 to 3 have good mechanical properties and corrosion resistance, as well as good environmental resistance. In particular, the comprehensive performance of the cable sheath prepared in Example 1 is the most outstanding. This is mainly because modified reinforcing agents and modified resins are added to the formula. The synergistic effect of the two improves the interfacial bonding strength between the basalt fiber and the resin matrix, thereby improving the comprehensive performance of the cable sheath.
[0094] However, because the necessary technical solutions are not adopted in Comparative Examples 1 to 10, the corresponding performance tests are significantly worse than those of the embodiments. In Comparative Example 1, the formula of the modified reinforcing agent is changed, and the basalt fiber is directly used in the cable sheath. It can be seen that the mechanical properties and corrosion resistance of the cable sheath prepared by it are significantly reduced, especially after low-temperature and high-temperature treatment, the performance of the cable sheath is more significantly reduced. This is mainly because although the basalt fiber itself has good mechanical properties, when applied to the cable sheath, the interface compatibility between the basalt fiber and the resin matrix is poor. In a low-temperature environment, the unmodified basalt fiber may make the composite material more brittle and hard, and thus prone to fracture. There may be defects in the interface between the untreated basalt fiber and the resin matrix. These defects are easy to become the starting point of corrosion under the action of the corrosive medium, reducing the corrosion resistance of the entire composite material. Comparative Example 1 proves that the modification of basalt fiber and its addition to the cable sheath formula has an important influence on environmental resistance.
[0095] In Comparative Example 2, only the basalt fiber was subjected to acid oxidation treatment, and no surfactant treatment was performed. From the results, it can be seen that the mechanical properties and corrosion resistance of the prepared cable sheath decreased, especially after treatment in high and low temperature environments, various properties also decreased significantly. This is mainly because although acid oxidation modification can improve the activity of the basalt fiber surface, without the help of surfactants, the interfacial bonding strength between the fiber and the resin matrix may not be sufficient to cope with stress changes under extreme temperature conditions. This may cause delamination or cracking of the composite material at high or low temperatures. In addition, without the assistance of surfactants, there may be more defects in the interface between the basalt fiber and the matrix after acid oxidation treatment. These defects will become the starting point of corrosion, thereby reducing the corrosion resistance of the composite material. Comparative Example 2 proves that acid oxidation treatment and surfactant treatment of basalt fiber have an important influence on the improvement of the comprehensive performance of cable sheaths.
[0096] In Comparative Example 3, only silicon dioxide is used to mix with the modified basalt fiber, and silicon carbide and titanium dioxide are not used. It can be seen from the results that the various properties of the prepared cable sheath are reduced. This is mainly because components such as silicon carbide and titanium dioxide help to adjust the thermal expansion coefficient of the composite material, so that the composite material can better adapt when the temperature changes. Using only silicon dioxide may cause mismatch in thermal expansion coefficients and affect the thermal stability of the composite material. Components such as silicon carbide and titanium dioxide can help improve the interfacial bonding between basalt fiber and matrix material. Using only silicon dioxide may not achieve the same bonding effect, thereby affecting the overall corrosion resistance of the composite material. Comparative Example 3 proves that mixing a variety of additives with the second modified basalt fiber can produce a synergistic effect and jointly improve the comprehensive performance of the cable sheath. Therefore, silicon carbide, silicon dioxide and titanium dioxide have an important influence on improving the comprehensive performance of the cable sheath.
[0097] The polyvinyl chloride (PVC) in Comparative Example 4 was not acid activated. From the results, it can be seen that the comprehensive performance of the cable sheath prepared therefrom is reduced. This is mainly because there may be more defects at the interface between the unactivated PVC and other components. These defects are easy to become the starting point of corrosion under the action of corrosive media, which makes the cable sheath more easily damaged under chemical erosion. Comparative Example 4 proves the importance of activating polyvinyl chloride.
[0098] In Comparative Examples 5 and 6, silicone rubber and high-density polyethylene in the modified resin were not added. From the results, it can be seen that the corrosion resistance, mechanical properties and environmental resistance of the cable sheath prepared therefrom all decreased to varying degrees. This is mainly because silicone rubber has good high temperature resistance, while HDPE helps to improve the low temperature resistance of the composite material. If these components are not added, the performance of the cable sheath under high and low temperature conditions may decrease, affecting its stability and reliability under extreme temperature conditions. This shows that there is a synergistic effect between the polyvinyl chloride, silicone rubber and high-density polyethylene in the present invention, which helps to improve the compatibility and interfacial bonding between the components in the composite material and reduce interface defects. The lack of these components will make the cable sheath more susceptible to erosion by corrosive media. Comparative Examples 5 and 6 prove that the modified resin has an important influence on the comprehensive performance of the cable sheath.
[0099] In the modified resin in Comparative Example 7, no initiator and grafting monomer are added. From the results, it can be seen that the comprehensive performance of the cable sheath prepared therefrom is reduced. This is mainly because the initiator (such as azobisisobutyronitrile) and the grafting monomer (such as epoxy acrylate) can promote the polymerization reaction and increase the degree of crosslinking between molecules, thereby improving the strength and toughness of the material. If these ingredients are not added, the mechanical properties of the cable sheath will decrease, resulting in easier breakage or deformation when subjected to external forces. Initiators and grafting monomers help to improve the compatibility and interfacial bonding between the components in the composite material and reduce interface defects. The lack of these components will make the cable sheath more susceptible to corrosion by corrosive media. Comparative Example 7 proves that modified polyvinyl chloride, silicone rubber and high-density polyethylene are very important for improving the comprehensive performance of cable sheaths under the conditions of initiators and grafting monomers.
[0100] In Comparative Example 8, only polyvinyl chloride is used as the resin matrix. Compared with Comparative Examples 4 to 7, the comprehensive performance of the cable sheath prepared therefrom is further reduced. This is mainly because there may be more defects at the interface between the unmodified PVC and other components. These defects are easy to become the starting point of corrosion under the action of corrosive media, which will lead to reduced corrosion resistance of the cable sheath. Unmodified PVC may soften or deform at high temperatures, affecting the performance of the cable sheath, which may cause the performance of the cable sheath to decrease under high temperature conditions. Unmodified PVC may become more brittle at low temperatures, which may affect the mechanical properties of the cable sheath, which will cause the performance of the cable sheath to decrease under low temperature conditions. Comparative Example 8 proves that the use of modified resin has an important influence on the comprehensive performance of the cable sheath.
[0101] Comparative Examples 9 and 10 respectively changed the types of polyethylene and silicone rubber in the modified resin. From the results, it can be seen that the comprehensive performance of the cable sheath prepared therefrom has decreased. This is mainly because the polyvinyl chloride, polyethylene and silicone rubber in the modified resin together constitute a specific cross-linked network, which improves the comprehensive performance of the sheath. In particular, high-density polyethylene has good toughness, which can further improve the mechanical properties of the cable sheath. Silicone rubber can improve the toughness of the composite material due to its elasticity (elongation ≥ 470%), making it less prone to brittle fracture when subjected to external forces. Comparative Examples 9 and 10 show that the types of polyethylene and silicone rubber play an important role in improving the comprehensive performance of the cable sheath. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0102] Therefore, the present invention adopts an aluminum alloy cable with the above structure and a preparation method thereof, and through the synergistic effect of modified basalt fiber and modified resin, significantly improves the performance of the cable sheath in many aspects, including mechanical properties, corrosion resistance, extreme temperature resistance, flame retardant properties and processing performance, thereby improving the overall reliability and service life of the cable.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. An aluminum alloy cable, comprising an aluminum alloy conductor and a sheath covering the aluminum alloy conductor. It is characterized in that The sheath comprises the following raw materials in parts by weight: 100-120 parts of modified resin; 45~55 parts of modifier and enhancer; 40~50 parts of inorganic filler; Flame retardant 5~30 parts; 10~20 parts of plasticizer; Antioxidant 0.1~3 parts; 0.5~1 part of lubricant; The preparation method of the modified reinforcing agent is: Concentrated sulfuric acid and water are mixed, and then hydrogen peroxide is added to obtain an acid oxidation solution, and then basalt cellulose is added to the acid oxidation solution, soaked at 60-90° C. for 2-4 hours, washed with deionized water until neutral, and dried to obtain a first modified basalt fiber; Add 3-5 parts of the first modified basalt fiber to a mixed aqueous solution formed by 1-3 parts of sodium α-olefin sulfonate and 1-3 parts of sodium cocoyl aminopropionate, soak at room temperature for 24-48 hours, take out, wash and dry, to obtain a second modified basalt fiber; 1-3 parts of silicon carbide, 4-6 parts of silicon dioxide and 1-3 parts of titanium dioxide are mixed to obtain a mixture, and then a mixed aqueous solution formed by 0.5-1.2 parts of γ-aminopropyltriethoxysilane is added to the mixture, and the mixture is stirred evenly to form a dispersion. Then, the second modified basalt fiber is added to the dispersion, and the mixture is reacted at 100-120° C. for 1-3 hours, and then naturally cooled to room temperature, filtered, washed, and dried to obtain a modified reinforcing agent.
2. The aluminum alloy cable according to claim 1, It is characterized in that The single fiber diameter of basalt fiber is 5.5~25μm and the length is 6~10mm.
3. The aluminum alloy cable according to claim 1, It is characterized in that According to parts by weight, the preparation method of the modified resin is: The polyvinyl chloride is added into a nitric acid solution and activated at 90-100°C for 3-5 hours, then washed with deionized water until neutral, and then dried at 80-100°C to obtain modified polyvinyl chloride; 10-20 parts of modified polyvinyl chloride, 5-10 parts of high-density polyethylene and 1-5 parts of silicone rubber are mixed, and then added into a twin-screw extruder for melt blending. During the extrusion process, 0.3-0.5 parts of azobisisobutyronitrile and 2-5 parts of epoxy acrylate are also added. The temperature of the twin-screw extruder is 180-220°C. After the mixture is cooled and formed, a modified resin is obtained.
4. The aluminum alloy cable according to claim 3, It is characterized in that The mass concentration of concentrated sulfuric acid in the acid oxidation solution is 30-40%, and the mass concentration of hydrogen peroxide is 10-15%; The mass concentration of sodium α-olefin sulfonate is 5~8%, and the mass concentration of sodium cocoyl aminopropionate is 5~8%; The mass concentration of γ-aminopropyltriethoxysilane is 1~3%; The mass concentration of nitric acid solution is 20~40%.
5. The aluminum alloy cable according to claim 1, It is characterized in that The inorganic filler is one or more of calcium carbonate, aluminum hydroxide and magnesium hydroxide.
6. The aluminum alloy cable according to claim 1, It is characterized in that The flame retardant is one or more of zinc borate, melamine phosphate and triphenylphosphonate.
7. The aluminum alloy cable according to claim 1, It is characterized in that The plasticizer is one or more of dioctyl adipate, dioctyl sebacate, and tri(2-hydroxyethyl)phosphine.
8. The aluminum alloy cable according to claim 1, It is characterized in that The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or 2,2-bis(4-hydroxyphenyl) propane.
9. The aluminum alloy cable according to claim 1, It is characterized in that The lubricant is one or more of PE wax, stearic acid, solid paraffin and calcium stearate.
10. A method for preparing an aluminum alloy cable according to any one of claims 1 to 9, It is characterized in that The following steps are involved: a) Add modified resin, modified reinforcing agent, inorganic filler, flame retardant, plasticizer, antioxidant and lubricant into a high-speed mixer, mix at 110-125°C for 5-8 hours to obtain a mixed material; b) At 150-200° C., the mixed material is extruded using an extruder and coated on the surface of the aluminum alloy conductor to form a sheath to obtain an aluminum alloy cable.
Citation Information
Patent Citations
Tensile polyvinyl chloride modified cable material and preparation method thereof
CN107674345A
Tensile polyvinyl chloride cable
CN107919190A
Wear-resistant charging pile cable and preparation method thereof
CN116612924A
Offshore photovoltaic cable insulating sheath material and preparation method thereof
CN118006025A
Heat-resistant modified polyvinyl chloride power tube and preparation method thereof
CN118126467A
Cited By
High-strength corrosion-resistant ship cable and preparation method thereof
CN119320538A
Braided insulation composite cable support and preparation method and application thereof
CN120896061A
